Essential Oils from Lamiaceae Species with potential Antifungal activity: a review (Research, Society and Development, 2022)
In recent years, the incidence of fungal infections has increased sharply. Candida yeasts are responsible for a wide variety of clinical manifestations, from urinary tract infections to bloodstream infections. An alternative to medicines are essential oils and their bioactive compounds, which can present a broad antimicrobial spectrum. There is a large amount of works in the literature that address the role of essential oils from plant species as potential sources of antimicrobial agents, including the anti-Candida action. The species of Lamiaceae are rich in essential oils, which show promising substances in the inhibition of Candida. This review raised articles published in the last five years (2016 to 2021) with the main anti-Candida activities of essential oils from representatives of Lamiaceae, in addition to highlighting their major components. The review consisted of data obtained from 56 articles which included 71 Lamiaceae plants. The essential oils of the species showed good anti-Candida activity (MICs